2014
DOI: 10.1111/echo.12702
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Total Atrial Conduction Time Measured with Tissue Doppler Imaging to Predict the Maintenance of Sinus Rhythm after External Electrical Cardioversion of Persistent Atrial Fibrillation

Abstract: The TACT using TDI is an independent predictor of AF recurrence and can be used to predict the maintenance of SR after external electrical CV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 36 publications
0
13
0
3
Order By: Relevance
“…17 AF has also been reported to be associated with slow LA conduction, even without detectable structural remodeling. 6,18 Prolonged PA-TDI has previously been reported to be associated with an increased risk of new-onset AF 19 and of AF recurrence after cardioversion 20 and RFCA. 21,22 Recently, Kojima et al reported that poor LA function assessed by velocity vector strain imaging echocardiography was associated with PAF, regardless of LA size.…”
Section: Discussionmentioning
confidence: 99%
“…17 AF has also been reported to be associated with slow LA conduction, even without detectable structural remodeling. 6,18 Prolonged PA-TDI has previously been reported to be associated with an increased risk of new-onset AF 19 and of AF recurrence after cardioversion 20 and RFCA. 21,22 Recently, Kojima et al reported that poor LA function assessed by velocity vector strain imaging echocardiography was associated with PAF, regardless of LA size.…”
Section: Discussionmentioning
confidence: 99%
“…to be predictors of the occurrence or recurrence of AF, [9][10][11][12][13][14][15][16][17] some other investigators have regarded them as early markers of LA structural remodeling. [44][45][46][47] ] Nevertheless, a fact that was overlooked in their studies is that the LA functions as a pump, too, and similar to any other contractile pumps requires synchronized contractions to produce an optimal output.…”
Section: Whereas Many Researchers Have Considered Acts and Liaemdmentioning
confidence: 99%
“…Tabela 10. Coeficientes de correlação (Coef) do intervalo PA-TDI médio com variáveis ecocardiográficas quantitativas normalizadas pelo peso em todos os animais e segundo o diagnóstico -São Paulo, 2018 ................................................. 64 Tabela 11 -Variáveis selecionadas na população que apresentou FA e população que não desenvolveu a arritmia -São Paulo, 2018 ................................................... 66 Tabela 12-Análise bivariada de parâmetros ecocardiográficos em relação à ocorrência de fibrilação atrial e ao tempo decorrido -São Paulo, 2018 .................. 67 Tabela 13-Análise multivariada de parâmetros ecocardiográficos em relação à ocorrência de fibrilação atrial -São Paulo, (MAFFÈ et al, 2015). Sua mensuração pode ser feita por diversas técnicas, sendo o padrão-ouro o estudo eletrofisiológico (ERDEM et al, 2016).…”
Section: Lista De Figurasunclassified
“…Em medicina, o TACT mensurado por meio da ecocardiografia tecidual é apontado como um forte preditor da ocorrência de fibrilação atrial (FA). Sua aplicabilidade já foi comprovada para prever a ocorrência dessa arritmia em pacientes em ritmo sinusal, após cardioversão elétrica da arritmia, após infarto agudo do miocárdio, cirurgia de revascularização coronariana, após procedimento de ablação por radiofrequência, dentre outros (DE VOS et al, 2009;DEN UIJL et al, 2011;FUJIWARA et al, 2014;MAFFÈ et al, 2015). (AMBROSI et al, 2012).…”
Section: Lista De Figurasunclassified
See 1 more Smart Citation